2003
DOI: 10.2337/diacare.26.7.2048
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL Cholesterol and Apolipoprotein B in the Dyslipidemic Classification of Type 2 Diabetic Patients

Abstract: OBJECTIVE -To compare non-HDL cholesterol (HDLc) and apolipoprotein B (apoB) in the identification of nonconventional high-risk dyslipidemic phenotypes in type 2 diabetic patients.RESEARCH DESIGN AND METHODS -Total cholesterol and triglycerides, HDLc, LDL cholesterol, non-HDLc, apolipoprotein B (apoB), and LDL size were determined in 122 type 2 diabetic patients (68% male, aged 59.6 Ϯ 9.7 years, and HbA 1c 7.5% [range 5.2-16.0]). They were then classified as normo-and hypertriglyceridemic if their triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…ApoB predicts mortality from cardiovascular disease even in the presence of normal or low non-HDL-cholesterol values. A detailed study has shown that measurements of ApoB provide a better estimate of small dense LDL particles, which are not detected by simple measurement of non-HDL-cholesterol [14]. Our findings are therefore consistent with those of others [8].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ApoB predicts mortality from cardiovascular disease even in the presence of normal or low non-HDL-cholesterol values. A detailed study has shown that measurements of ApoB provide a better estimate of small dense LDL particles, which are not detected by simple measurement of non-HDL-cholesterol [14]. Our findings are therefore consistent with those of others [8].…”
Section: Discussionsupporting
confidence: 93%
“…As small, dense LDL particles, which are strongly associated with cardiovascular disease, contain less cholesterol than large buoyant LDL, measurement of LDLcholesterol will clearly result in underestimation of the risk due to LDL [13,14]. To overcome this limitation and to take into account the cholesterol in VLDL, the Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (Adult Treatment Panel III) recommended that non-HDL-cholesterol be used instead of LDL-cholesterol for people with the metabolic syndrome [15].…”
Section: Introductionmentioning
confidence: 99%
“…High non-HDL-cholesterol levels are an indicator of vascular risk [25] and the National Cholesterol Education Program Adult Treatment Panel III guidelines now spe- cifically recommend therapy in patients with hypertriglyceridaemia [17]. Changes in non-HDL-cholesterol (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Atherogenic dyslipidemia which is one of the most important component of MetS is associated with increased risk of cardiovascular disease [8]. Accordingly, two approaches had been used in this study to investigate the abnormality in the lipid profiles among both obese and MetS patients, by determining ox-LDL-C, a marker of lipoprotein-associated oxidative stress, and non HDLC, and their response after using the two different dietary methods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, measurement of Apo B provides direct information on the number of atherogenic particles (LDL and non LDL), irrespective of their size. Further, these atherogenic particles, collectively known as non-HDL lipoproteins, are associated with atherogenic dyslipidaemia, insulin resistance, portal hyperinsulinemia and metabolic syndrome [8,9].…”
Section: Introductionmentioning
confidence: 99%